Activation of the E2F transcription factor in adenovirus-infected cells involves E1A-dependent stimulation of DNA-binding activity and induction of cooperative binding mediated by an E4 gene product. - Raychaudhuri, P (1990)
Previous experiments have demonstrated that the DNA-binding activity of the E2F transcription factor is increased upon adenovirus infection and that both the E1A and E4 genes are required for activation. In this study, we demonstrated that this enhanced binding of E2F to the E2 promoter is the result of two events. (i) There is stimulation of the DNA-binding activity of the E2F factor; this stimulation is E1A dependent but independent of E4. (ii) There is also induction of a stabilized interaction between E2F molecules bound to adjacent promoter sites; induction of stable E2F binding requires E4 gene function. This two-step activation process was also demonstrated in vitro. A heat-stable fraction from extracts of adenovirus-infected cells, which contains the 19-kilodalton E4 protein, was capable of stimulating stable E2F binding in an ATP-independent manner and appeared to involve direct interaction of the E4 protein with E2F. An extract from virus-infected cells devoid of the E4 19-kilodalton protein stimulated E2F DNA binding without forming the stable complex. This reaction required ATP. We conclude that activation of E2F during adenovirus infection is a two-step process involving a change in both the DNA-binding activity of the factor and the capacity to stabilize the interaction through protein-protein contacts.